Mechanism of profit management at the enterprises in financial globalization conditions - Khalatur, Svetlana; Халатур, Світлана Миколаївна; Plisko, Irina; Пліско, Ірина Геннадіївна (Переяслав-Хмельницький державний педагогічний університет імені Григорія Сковороди, 2018)
Subject of research – conceptual, theoretical-methodological and scientific-practical principles of profit management at enterprises. Aim of research is to investigate and describe the mechanism, factors, reserves and ways to increase the profitability of enterprises of the national economy of Ukraine in the conditions of financial globalization. Methods of research. The article uses a set of methods of scientific research: statistical, historical, normative, analytical. From the methodological point of view, we note that this analysis refers to the period 2010-2017 years. Results of research. Having studied the ways to increase the profitability of enterprises in the market conditions, we can conclude that due to the lack of an effective business model for increasing the company's profitability in most of the enterprises of the national economy of Ukraine, there is a risk of shortfall in profits or even losses. It is argued that enterprises need to form an optimal business model for increasing profitability before performing financial and corporate activities in order to achieve the desired results. The problem is that many businesses use the concept of a business model and business strategy as interchangeable, which is not correct. Application of results. The results of this study can be applied in the practice of financial and economic activity of enterprises of the national economy of Ukraine. Conclusions. In order for the company to grow and profit, it is very important that it has a reliable business model as well as a competitive strategy on how to differ from competitors. It is important to combine business model analysis with strategic analysis when an enterprise develops and implements a new business model to protect the results of a transformed business model from the point of view of competitive advantage. This link involves segmentation of the market, creating value propositions for each segment, and developing a variety of «isolation mechanisms» that will help avoid simulating business models / business strategies by competitors. In order to create and maintain a competitive advantage, and thus increase the profitability of the enterprise, differentiated and difficult to immitate, at the same time effective design for the business model of the enterprise is very important. Предмет дослідження – концептуальні, теоретико-методологічні й науково-практичні засади управління прибутком на підприємствах. Мета дослідження – дослідити та описати механізм, чинники, резерви та шляхи підвищення рівня прибутковості підприємств національної економіки України в умовах фінансової глобалізації. Методи дослідження. У статті застосовано сукупність методів наукового дослідження: статистичний, історичний, нормативний, аналітичний. З методологічної точки зору, відзначимо, що даний аналіз посилається на період 2010-2017 років. Результати роботи. Провівши дослідження шляхів підвищення прибутковості підприємств в умовах ринку, можна зробити висновок, що через відсутність у більшості підприємств національної економіки України ефективної бізнес-моделі підвищення прибутковості підприємства, існує загроза недоотримання прибутків або взагалі отримання збитків. Стверджується, що підприємствам необхідно сформувати оптимальну бізнес-модель підвищення прибутковості перед виконанням фінансово-господарської діяльності для того, щоб досягти бажаних результатів. Проблема полягає в тому, що багато підприємств використовують концепцію бізнес-моделі та бізнес-стратегії як взаємозамінні, що не є правильним. Галузь застосування результатів. Результати цього дослідження можуть бути застосовані у практиці фінансово-господарської діяльності підприємств національної економіки України. Висновки. Для того, щоб підприємству розвиватися і отримувати прибуток, дуже важливо, щоб у нього були і надійна бізнес-модель, а також конкурентоспроможна стратегія щодо того, як відрізнятися від конкурентів. Існує важливість об'єднання аналізу бізнес-моделі зі стратегічним аналізом, коли підприємство розробляє та реалізує нову бізнес-модель для захисту результатів трансформованої бізнес-моделі з точки зору конкурентних переваг. Цей зв'язок включає сегментацію ринку, створення цінності пропозиції для кожного сегмента та розробка різноманітних «ізоляційних механізмів», які допоможуть запобігти імітації бізнес-моделі / бізнес-стратегії конкурентами. Для того, щоб створити та підтримати конкурентну перевагу, а отже, підвищити прибутковість підприємства, диференційований і важко піддаваємий наслідуванню, одночасно ефективний дизайн для бізнес-моделі підприємства є дуже важливим.
Механізм управління прибутком на підприємствах в умовах фінансової глобалізації
Keywords: business model; бізнес-модель; competitors; конкуренти; profitability; рентабельність; economic development; економічний розвиток; national economy; національна економіка